Modelling the acceleration and deceleration profile of elite-level soccer players - Newans, T.; Bellinger, P.; Dodd, K.; Minahan, C. (International Journal of Sports Medicine, 2019)
The ability to change velocity rapidly is a key element of field-based sports. This study quantified the acceleration and deceleration profiles of soccer players during match play. Global positioning system measures were collected from 20 male soccer players competing in the Australian Hyundai A-League during 58 matches. Match data were organized into ten 9 min periods (i.e., P1: 0-9 min) and the time spent at moderate (1-2 m·s-2) and high (>2 m·s-2) acceleration and deceleration thresholds were quantified. Additionally, a novel deceleration: acceleration ratio was quantified to identify the transient nature of deceleration activity. Linear mixed models were used to model the acceleration and deceleration profiles. All acceleration and deceleration metrics displayed negative logarithmic curves within each half. There was no change in the ratio of high deceleration: acceleration; however, a significant increase in the ratio of moderate deceleration:acceleration was evident. Using negative logarithmic curves to illustrate the acceleration and deceleration decay provides a novel methodological approach to quantify the high-intensity actions during match play. A decrease in the time spent decelerating throughout a match may be attributed to a lack of opportunity. Practitioners can use the coefficients, intercepts, and deceleration: acceleration ratios to monitor a player`s deceleration profile in match play.